(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This research paper delves into the transformative power of ethical leadership in cultivating and enhancing organizational culture. As global businesses navigate increasing ethical challenges and stakeholder expectations, the presence of principled leadership becomes essential. Ethical leaders influence the organization's ethical climate by exemplifying integrity, fairness, and accountability. This study synthesizes secondary data drawn from scholarly literature, industry reports, and case studies to examine the dynamic interplay between ethical leadership and cultural evolution within organizations. Key findings suggest that ethical leadership not only nurtures trust and transparency but also aligns employee behavior with organizational values, driving performance, commitment, and long-term sustainability. Ultimately, this research highlights ethical leadership as a critical enabler of resilient and adaptive corporate cultures.